Education for Sustainable Development in the Value System of Teachers - Galtseva, Tetyana; Svitich, Svitlana; Kutsiy, Andriy; Savchenko, Victoria; Strukova, Tetyana (European Journal of Sustainable Development, 2020)
?ducation for sustainable development shows all the necessary from sustainable development concept in unity of ecologic, social-cultural, and economic spheres. The reduction of education for sustainable development to the issue of environmental education poses a threat to the values ??associated with the humanistic interpretation of education. Firstly, it is the absolutization of environmental values and the lack of effective synthesis of these values with social values, and economic values partly. Secondly, there is a lack of needs and values of teachers and value-methodological principles of integration of environmental and humanistic values. Thirdly, to a large extent on the periphery of education for sustainable development are the problems of transformation of society itself, social relations, culture, ways of communication, interaction of people with each other, as well as the emotional component of such interaction. One of the possible ways to solve these problems can be considered the formation of new, more adapted to the needs of sustainable development of value-cognitive characteristics of teachers. The new model of education should provide a focus on people as the main object of sustainable development, subordinating value changes to the task of socialization and humanization of social development, taking into account environmental constraints. Based on the results of the study, it is necessary to pay attention to the development of social intelligence, emotional intelligence, communicative intelligence and practical intelligence. For more adequate training of professionals in the field of education for sustainable development, it is advisable to expand cooperation with governmental and non-governmental organizations. Key words: education, sustainable development, humanism, ecology, training, values, social intelligence